(3GdLdjS GdUGdM GdcGaj hGdCfjS GdfGUM GdTGajs - (3GdeYGaj Hf RcQjG Hf jMji GdLQjQqj GdfgQhGfj, nCoHh GdnanQL GHf WQGQ,J (B390 (3g` s ((3jMji Hf egOj Hf eMeO s)
(3ChdgG (B:s
(3CeG HYO(B: (3aEfj efP eOI eVJ hoSfqjI NdJ acQJ aj CTjGA ef YLGFH Ndb Gddg hMceJg hCjGOjg hfYeJg Ke JWdYJ Edi LdjS aCYhRfj Ph dH YGbd s
(3BNQgG (B:s
(3hef TQM eNJUQ CHj YeQh GdLQej aj GdfMh hCKHJfG efg HeG dG fYed CMO SHbfG Edjg hef fXQ ajeG gfGdc JHjf eG hUafGg Ef TGA Gddg JYGdi s
(3GfXQ GdLRA GdChd HGdCQbGe (B168-170 (3COHs
(3HBNQgG ebGHdI SfI (B1083s
(3heWGdYI SfI (B1304(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs